Harnessing monocyte-derived dendritic cells for evaluating T cell response by mixed leukocyte reaction - Honorio Torres-Aguilar; Sorely Adelina Sosa-Luis; Alexia Almaraz-Arreortua; William de Jesús Ríos-Ríos (Exploration of Immunology)
The mixed leukocyte reaction (MLR) is a pivotal in vitro assay for evaluating T-cell responses stimulated by allogeneic antigen-presenting cells (APCs). Dendritic cells (DCs) are the most efficient stimulatory cells. However, the scarcity of circulating DCs in peripheral blood limits their isolation for research or clinical use. In contrast, monocytes, which are abundant and easily accessible, can be differentiated into monocyte-derived DCs (moDCs) in vitro and have emerged as the most practical and efficient stimulatory cells for MLR due to their accessibility and robust allostimulatory capabilities. This review aims to describe the scientific rationale and evidence for using moDCs in MLR assays to assess T-cell alloreactivity. Its methodology outlines the protocols for experimental, preclinical, and biosafety assays that have demonstrated the practicality of moDCs in evaluating and quantifying the alloresponse of naïve and memory CD4+ and CD8+ T cells, as well as the effects of immunomodulatory factors, immune monitoring, and tolerogenic strategies in the context of transplantation. Additionally, it illustrates how moDC-mediated MLRs have provided critical insights into understanding alloimmunity processes and antigen-specific T-cell responses in cancer immunotherapy, autoimmune diseases, and vaccine development, with potential implications for personalized medicine and immunotherapy optimization. In conclusion, despite ongoing challenges such as standardization and scalability in massive cell production, the current understanding and reproducible results of moDC applications in MLRs highlight their potential to develop innovative strategies focused on immune monitoring.